Management of cardiovascular risk in patients with rheumatoid arthritis: evidence and expert opinion - van den Oever, Inge A.M. (SAGE Publications, 2013)
The risk of cardiovascular morbidity and mortality is increased in rheumatoid arthritis. The classical cardiovascular risk factors, including smoking, hypertension, dyslipidaemia, insulin resistance and diabetes mellitus, obesity and physical inactivity do not appear to explain the excess cardiovascular risk in rheumatoid arthritis, although they do contribute, albeit in a different way or to a lesser extent, to rheumatoid arthritis in comparison with the general population. A very important link between rheumatoid arthritis and cardiovascular disease is inflammation as it plays a key role in all stages of atherosclerosis: from endothelial dysfunction to plaque rupture and thrombosis. It also has an influence on and accentuates some traditional cardiovascular risk factors, such as dyslipidaemia, obesity and insulin resistance. To date, the exact pathophysiologic mechanism by which this relation between cardiovascular disease and rheumatoid arthritis can be explained is not completely clear. Cardiovascular risk management in rheumatoid arthritis is mandatory. Unfortunately, the way this should be done remains a point of discussion. In this review issues regarding cardiovascular risk in rheumatoid arthritis and its management will be addressed, according to evidence presented in the latest studies and our own experience-based opinion.